2016
DOI: 10.2147/ott.s115631
|View full text |Cite
|
Sign up to set email alerts
|

FAS and FASL genetic polymorphisms impact on clinical outcome of malignant pleural mesothelioma

Abstract: BackgroundFAS-670 A>G (rs1800682) and FASL-844 C>T (rs763110) polymorphisms have been previously correlated with clinical outcome of non-small cell lung cancer (NSCLC) and breast and bladder cancers. We investigated the influence of these polymorphisms on clinical outcome of malignant pleural mesothelioma (MPM) patients.Patients and methodsIn this cohort study (NCT02269878), 68 epithelioid MPM Egyptian patients treated with first-line platinum-based chemotherapy were recruited in the period between April 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Previous investigations demonstrated that those functional genetic variations of Fas/FasL/CASP8 may influence the susceptibility to gastric cancer or affected the sensitivity to platinum-based chemotherapy for some types of cancer, including non-small-cell lung cancer, malignant pleural mesothelioma and so on [29][30][31]. However, the associations between genomic variants involved in Fas-mediated apoptosis pathway, with the response to platinum-based chemotherapy for gastric cancer patients, was still unclear.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Previous investigations demonstrated that those functional genetic variations of Fas/FasL/CASP8 may influence the susceptibility to gastric cancer or affected the sensitivity to platinum-based chemotherapy for some types of cancer, including non-small-cell lung cancer, malignant pleural mesothelioma and so on [29][30][31]. However, the associations between genomic variants involved in Fas-mediated apoptosis pathway, with the response to platinum-based chemotherapy for gastric cancer patients, was still unclear.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“… 22 FASL-844 polymorphism could predict progression free survival (PFS) in MM patients receiving platinum based chemotherapy. 23 Polymorphisms in REV1 and REV3L were also associated with the outcome of cisplatin based chemotherapy in MM. 24 The results of the study showed that DNA repair gene polymorphisms XRCC1 may modify the response to gemcitabine-platinum combination chemotherapy in MM patients.…”
Section: Introductionmentioning
confidence: 96%